2001
DOI: 10.1590/s0004-28032001000200004
|View full text |Cite
|
Sign up to set email alerts
|

Antiendomysium antibodies in brazilian patients with celiac disease and their first-degree relatives

Abstract: -Background -Literature data have shown high specificity of antiendomysial antibodies (EmA IgA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
5
19
1
3
Order By: Relevance
“…The prevalence of CD in first-degree relatives of patients with CD undergoing intestinal biopsy varies from 5.5% [29] to 22.5% [30] . In a previous study with 115 Brazilian relatives, we reported 15.6% CD prevalence [5] , with female preponderance, and in the present study there was 3.8% of test positivity (Table 2) [31] . All were female: 1 sister and 1 daughter of the same family; 1 mother.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The prevalence of CD in first-degree relatives of patients with CD undergoing intestinal biopsy varies from 5.5% [29] to 22.5% [30] . In a previous study with 115 Brazilian relatives, we reported 15.6% CD prevalence [5] , with female preponderance, and in the present study there was 3.8% of test positivity (Table 2) [31] . All were female: 1 sister and 1 daughter of the same family; 1 mother.…”
Section: Discussionsupporting
confidence: 71%
“…The first-degree relatives of the patients were invited to participate in the study by phone call [5] . Patients with clinical complaints suggestive of CD were submitted to the point-of-care test and to intestinal biopsy plus IgA EmA determination for comparison [18] .…”
Section: Issn 1007-9327 Cn 14-1219/r World J Gastroenterol September mentioning
confidence: 99%
See 1 more Smart Citation
“…The disease may present a wide clinical spectrum, from malabsorption syndrome to extra-intestinal presentations, and can be atypical or asymptomatic (25,74) . Serologic tests are useful for screening and histological abnormalities confirm the diagnosis (38,74) . CD is associated with autoimmune disorders and can cause complications and death.…”
Section: Introductionmentioning
confidence: 99%
“…The first, by NUNES et al (24) disclosed a prevalence of 0.8% among a group of 121 relatives. The main focus of the second study, by KOTZE et al (16) was to determine specificity and sensitivity of the antiendomysium antibody test performed on cryostatic sections of human umbilical cord, in a group of confirmed celiac patients and their first-degree relatives. Among the 18 serological positive first-degree relatives seven agreed to underwent intestinal biopsy.…”
Section: Introductionmentioning
confidence: 99%